Castanheiro do vento (Horta do Douro, Vila Nova de Foz Côa) : alguns apontamentos acerca do dispositivo arquitectónico - Vale, Ana Margarida (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This paper aims to reflect upon the architectonic devices present in the archaeological site of Castanheiro do Vento. In this way two particular structures will be considered as paradigmatic examples (after Agamben, 2000), and two concepts will be highlighted: immersion and movement.